Inequality of Development between Regions: Analysis its Influence on Regional Economic Growth in South Sulawesi Province - Sulpiani; Nurfadilla; Mirta Pakambanan; Nurazizah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to investigate uneven development between regions and its influence on regional economic growth in South Sulawesi Province. The main focus is on the comparison of regional development indices in various districts/cities in the province as well as the correlation between uneven development and regional economic growth. The data analyzed includes trends in the increase in HDI and GDP per capita ADHB from 2015 to 2019, with districts/cities such as Makassar, East Luwu and Enrekang showing the highest indices. Another important finding is that there is a significant correlation between uneven development (measured by the Williamson Index) and regional economic growth in the region. The implication is that more inclusive and equitable policies are needed to reduce development disparities between regions and encourage sustainable economic growth in South Sulawesi Province.